Awareness On Application Of Artificial Intelligence In Medicine Among Dental Students - A Survey - V, RANJANA; GAYATHRI, R; PRIYA, V VISHNU; KAVITHA, S KAVITHA (The journal of contemporary issues in business and government, 2021)
Aim and introduction:Artificial intelligence (AI) is one of the branches of computer science, which is capable of analyzing complex medical data. This technology is helpful in diagnosing disease, treatment, and predicting outcomes in many clinical scenarios. Artificial intelligence is nothing but a natural language processor and does repetitive jobs in a timely manner. Some disadvantages of AI technology are high initial capital requirement, potential for increased unemployment, which shows that this technology has the potential to replace physicians in future. The main aim of this survey is to assess the awareness on application of artificial intelligence in medicine among dental students. Materials and Method:Self-administrated questionnaire was designed based on awareness. The questionnaire was distributed through an online Google forms link. The study population included dental students belonging to the 18 – 26 age group. Method of representation of each output variable was in pie charts and bar graphs. The statistics done using SPSS software, chi square test was done to check the association and a p value of 0.05 was said to be statistically significant. This survey has been completed in the month of may 2020. Result:56% of the participants were aware that artificial intelligence is the analysis of medical data without direct human input. From the survey it was evident that 57% of the participants feel that with the help of AI clinical decision and diagnosis can be revolutionized and also found that both male and female students were equally aware of the importance of application of artificial intelligence in medicine(p-value>0.05). Conclusion:This study concludes that about 59% of the study participants were aware that Artificial Intelligence technology in medicine is beneficial to doctors and also found that both male and female students were equally aware of artificial intelligence. Since AI technology has the potential to develop into an innovative platform which is capable of analyzing more complex medical data, more awareness has to be created for better understanding and analysis of this technology.